Contribution of phenolic compounds and hormones in antioxidant defense responses of wild and cultivated barley genotypes under drought and heat stress - Farzaneh Karamzadeh; Ahmad Arzani; Ghodratollah Saeidi (Scientific Reports)
Abstract Drought and heat are major co-occurring stresses that sharply reduce crop yield. This study investigated antioxidant and hormonal responses in 36 barley genotypes (5 cultivated, 31 wild) under two planting dates and two irrigation regimes over two years. Evaluated traits included phenolic compounds, antioxidant enzymes, oxidative markers, DPPH activity, grain yield, and levels of ABA, IAA, and gibberellin. Under normal conditions, cultivated genotypes yielded 71% more than wild genotypes; however, this advantage declined to 12% under combined drought and heat stress. Under this extreme stress, yield reduction averaged 57% in wild genotypes and 72% in cultivated ones. Wild genotypes exhibited stronger antioxidant responses, marked by greater increases in guaiacol peroxidase, total phenolic content, total flavonoid content, and DPPH activity. Under drought and combined heat and drought stress, ABA increased significantly more in wild genotypes (>90%) than cultivated ones (>20%). In contrast, heat stress alone had no significant effect on ABA levels in either genotype. IAA and gibberellin showed a similar pattern, but with a declining trend. Ellagic acid, syringic acid, and rutin were the dominant phenolics contributing to stress tolerance. These results highlight wild barley’s superior stress adaptation through antioxidant and hormonal responses, offering valuable genes for improving cultivated barley.